A Review of Non-surgical Strategies for Managing Chronic Rhinosinusitis - Setiawan , Gunawan Wijaya (Journal of Society Medicine, 2025)
Chronic rhinosinusitis (CRS) remains a significant public health challenge, characterized by persistent inflammation of the sinonasal mucosa lasting at least 12 weeks, leading to symptoms such as nasal congestion, facial pain, rhinorrhea, and olfactory dysfunction. Affecting an estimated 5-12% of the global population, CRS imposes considerable economic and quality-of-life burdens. While surgical options like functional endoscopic sinus surgery (FESS) are effective for refractory cases, non-surgical management is the initial and often primary approach, emphasizing symptom control, inflammation reduction, and prevention of disease progression. This comprehensive review synthesizes evidence from recent guidelines, clinical trials, and observational studies on non-surgical strategies, including nasal saline irrigation, intranasal and systemic corticosteroids, antibiotics, biologics, and adjunctive therapies. Key advancements include precision medicine via endotyping and the integration of biologics for type 2 inflammation-dominant phenotypes, particularly in CRS with nasal polyps (CRSwNP). Drawing from updated 2024-2025 literature, we highlight personalized treatment algorithms to optimize outcomes, minimize adverse effects, and reduce the need for surgery.